Functional Foods - Minggawati Lai, Ratna (Jurnal Teknologi Pangan dan Gizi, 2000)
As we are moving into the 21st century, the world’s demand for food is becoming ever greater. In the poorest nations, the lack of availability of food supply leading to micronutrient deficiencies. In contrast, in developed countries, people enjoy a greater varieties and quantity of foods leading to the effect to overnutrition (obesity, heart disease, and cancer). In response, the concept of food is changing from an emphasis on health maintenance to promoting better health by helping to prevent chronic illness. Functional foods are design to help people to rerduce their risks of some diseases (by preventing) through readily available, good-tasting diets rather than through the use of curative measures only. The distribution of potential ingredients in functional foods are dietary fiber (40 %), calcium (20 %), oligosaccharides (20 %), lactic acid bacteria (10 %) and other (10 %). The perspective of Western and Eastern, somehow, are not totally competent. People living in the Eastern hemisphere believe that certain food had a therapeuticbenefit. Whereas those living in Western are considered to be more conscious in their health. The food industries and government agencies have the agreement to establish definition and substantiation for functional food. This aims to protect the consumer and build consumer confidence.